On the Enduring and Fleeting Uses of the Teaching Statement - McElroy, Kelly (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2023)
A teaching statement offers a written summary of one’s beliefs, approaches, and successes in teaching. In this article, I use the teaching statement that I wrote in library school as an autoethnographic artifact to consider my own development as a teacher, and to reflect on the teaching statement as a genre. How do we declare ourselves as teachers, and how does that identity develop and shift over time? I conclude with considerations of how a teaching statement can serve academic librarians.